Analysis of spoilage change over improvements on decorator machines with quality control groups (Pareto and fishbone diagrams) - Asep Saepudin; Aris Setiawan; Hilman Sholih; Aswin Domodite (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
Every company, including PT, has goals they'd like to accomplish. One of the businesses in the two-piece can sector is CPC. Up until now, PT's goal has been to switch products. The CPC is still not fulfilled; specifically, from January 2022 to May 2023, the product replacement time is still 42 minutes, resulting in the waste of 1043 cans, although the objective was set at 30 minutes for the replacement of the product and 800 cans for spoiling (wasted cans). The current issue is that 800 cans are wasted, and the goal product replacement time is 30 minutes. A quality control group was employed in this study's methodology (Pareto and fishbone diagrams). The primary goal of this study is to identify the underlying cause of the 42-minute product replacement time and the wasted 1043 cans. The analysis's findings demonstrated that the issue of resetting the plate is the one that frequently arises while switching out products. Several underlying causes of the reset plate issue were discovered after additional investigation, one of which was the unclear marking on the plate, which led to imprecise results when the plate was installed on the cylinder. Damages the can printing and necessitates a second plate installation, which wastes time and leads to spoilage. Consequently, a repair plan was created and put into action by changing the plate's markings to make installation easier to understand. This led to a quicker process of replacing the product (41 minutes before repair, 32 minutes after repair), as well as a decrease in the number of wasted cans (850 cans before repair, 828 cans after repair).